PENINGKATAN KEMANDIRIAN SISWA TUNARUNGU MELALUI PELATIHAN PEMBUATAN BATIK ECOPRINT - Arumita Wulan Sari,; Ismillah, Tanziyhan Li; Mufidah, Siti Nur; Indriana, Sri Wiji; Multiana, Ayun; Mahmudah, Siti (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
Having equal opportunities in terms of education and decent work should be owned by persons with disabilities. Different abilities possessed by persons with disabilities often led to negative perceptions from society. It made them less likely to get the main opportunity to get a decent job. Therefore, training was needed that is able to provide skills. Thus, people with disabilities got equal opportunities in getting decent jobs, and they could develop the independence of people with disabilities which were often considered low. This activity provided training on making Eco-print batik for deaf students as a skill set. This training was focused on developing aspects of student independence. Activities were carried out using online and offline methods that still followed the health protocols. The purpose of this activity was to develop students' skills in making Eco-print batik works. This was indicated by the success of students in creating Eco-print batik works. In addition, it was also intended to develop the independence of deaf students. The increase in students' independence was shown by pre-test and post-test questionnaires that were filled out by the students' parents. In the results of the pre-test students would be divided into 3 categories. Those were less independent, moderately independent, and independent. Meanwhile, in the post-test, students would be categorized as quite independent and independent. In conclusion, Eco-print batik training can be an alternative activity that can have a positive impact on increasing student independence.